Raman and photoluminescence properties of ZnO nanowires grown by a catalyst‐free vapor‐transport process using ZnO nanoparticle seeds. Issue 5 (8th January 2016) - Güell, Frank; Martínez‐Alanis, Paulina Raquel; Khachadorian, Sevak; Rubio‐García, Javier; Franke, Alexander; Hoffmann, Axel; Santana, Guillermo
Abstract : We report the synthesis of ZnO nanowires by a catalyst‐free vapor‐transport process on SiO2 /Si substrates. A modification of the method was performed using small ZnO nanoparticles (∼5 nm) in low concentration suspensions. The use of dichloromethane or toluene in the suspensions influences the nanoparticle distribution over the surface. The obtained nanowires have diameters ranging from 20 to 100 nm and lengths from 0.5 to 1 µm. Raman scattering results show a narrow (∼7 cm −1 ) full width at half maximum of the E2 high optical phonon mode, which demonstrate a good‐crystal quality of the ZnO nanowires obtained. Room temperature photoluminescence measurements show a broad emission band in the visible range at 430–830 nm, which is attributed to intrinsic defects. A notable decrease of this visible band was achieved making this method suitable for almost defect‐free ZnO nanowires. The photoluminescence results at 5 K demonstrate the role of surface defects as responsible for the visible band.